Factors That Influence the Compliance of Professional Nutrition Care Providers (PPA) in Providing Education to Patients and Families at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City - Lidya Paramitha Moha; Srikit S. Nurkamiden; Fri Sandria Riski Daud (West Science Social and Humanities Studies, 2024)
Professional Care Providers (PPA) as an interdisciplinary team play a role in maximizing the implementation of patient-focused services, one of which is through providing education. Education is carried out to help patients and their families better understand the health problems they are facing. PPAmust comply with professional norms and ethics in providing education to patients and their families. This research aims to analyze the influencing factorsPPA Nutrition compliance in providing education to patients and families at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City using descriptive research typequantitative approach. The data collection method was carried out through distributing questionnaires to Nutrition Care Professionals (PPA) at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City. The research results showed that predisposing factors (knowledge and attitudes), enabling factors (infrastructure, work environment and socialization), and reinforcing factors (role of management and policy) obtained measurement results (score > 50%). Of these three factors, the predisposing factor is the factor that most influences the level of PPA Gizi compliance in providing education to patients and families at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City.